PERANCANGAN GAME EDUKASI PENGENALAN PENGELOMPOKAN HEWAN BERDASARKAN MAKANAN BERBASIS ANDROID - Candra, Doli; Karnadi, Very (Computer Science and Industrial Engineering, 2020)
Animal grouping can be done based on the type of food, grouping consists of herbivores, carnivores and omnivores. The purpose of this study is to design and approve an android-based educational game application, it is needed to assist students in learning that is managed or at home. In this game students can distinguish and match animals based on food. In the process of making this application, researchers used the waterfall method, in this installation, namely requerment, design, implementation, verification, and maintenance. To build the android application, researchers used supporting software, namely construct2. In the process of collecting data, researchers use the method of literature study, and interviews.